2010
DOI: 10.1089/jpm.2010.0100
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Patients with Advanced Lung Cancer Regarding the Involvement of Family and Others in Medical Decision-Making

Abstract: Objective: To explore the preferences of competent patients with advanced lung cancer regarding involvement of family and/or others in their medical decision-making, and their future preferences in case of loss of competence. Methods: Over 1 year, physicians in 13 hospitals in Flanders, Belgium, recruited patients with initial non-smallcell lung cancer, stage IIIb or IV. The patients were interviewed with a structured questionnaire every 2 months until the fourth interview and every 4 months until the sixth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…2,13], and DM [13][14][15]; and also reveal that family caregiver involvement in DM is variable both across consultations and among different triads [13]. Family caregiver involvement in DM can vary on a spectrum from passive to dominant [4,16,17] and the form/extent of involvement may be influenced by contextual factors such as the patient's age, gender, health status, cultural background and relationship with the family caregiver [11,18]. Despite the growing empirical evidence base, there remains limited conceptual description of family caregiver involvement in DM.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…2,13], and DM [13][14][15]; and also reveal that family caregiver involvement in DM is variable both across consultations and among different triads [13]. Family caregiver involvement in DM can vary on a spectrum from passive to dominant [4,16,17] and the form/extent of involvement may be influenced by contextual factors such as the patient's age, gender, health status, cultural background and relationship with the family caregiver [11,18]. Despite the growing empirical evidence base, there remains limited conceptual description of family caregiver involvement in DM.…”
Section: Introductionmentioning
confidence: 93%
“…For example, family caregiver involvement in DM is increased among married/de-facto patient-caregiver pairs compared to other caregivers [11,18], and when caregivers report a close and strong relationship with the patient [4].…”
Section: Concept 5: Many Factors May Affect the Form And Extent Of Famentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] Among patients with advanced lung cancer in Belgium, Pardon et al reported that patients' family members regularly attended consultation and treatment appointments in order to provide emotional support, request further information and participate in the TDM process. 10 A large, multiregional, prospective cohort study of newly diagnosed patients with lung and colorectal cancer undertaken in the USA found that most participants involved family members in treatment decisions. 11 Nevertheless, the study concluded that further research is required to evaluate the impact such involvement might have on patient outcomes.…”
mentioning
confidence: 99%